2020
DOI: 10.2741/s539
|View full text |Cite
|
Sign up to set email alerts
|

Anti-atherosclerotic and cardiovascular protective benefits of Brazilian nuts

Abstract: Introduction 3. Epidemiological aspects 4. Atheroprotective effect of constituents of Brazil nuts 4.1. Dietary intake of Brazil nuts and protection against atherosclerosis 4.2. Dietary fiber and atherosclerosis 4.3. The atheroprotective effect of micronutrients of Brazil nuts 4.3.1. Magnesium (Mg) 4.3.2. Selenium (Se) 4.4. Arginine and other amino acids 4.5. Fatty acids, phytosterols, and sphingolipids 4.6. Tocopherols 4.7. Polyphenols 5. Summary and perspectives 6. Acknowledgements 7. References Atheroprotect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 94 publications
0
12
0
Order By: Relevance
“…Noteworthy is the fact that in DICA-NUTS trial all nuts provided will be acquired from local farmer's cooperatives and small producers; if effective, the study may contribute also to local economic growth by stimulating the consumption of foods locally cultivated. Nut consumption has been related to reducing the severity of atherosclerosis [49][50][51] by acting on intermediary mechanisms such as improving endothelial function, lipid metabolism, and glycemic markers, protecting both DNA and LDL-c from oxidation, decreasing inflammation, altering microbiota, and controlling body weight [52][53][54]. Nuts and seeds may improve serum lipids by reducing cholesterol absorption, increasing bile acid production by stimulation of 7-hydroxylase, inhibiting HMG-CoA reductase, and reducing postprandial lipidemia by their poor lipid bioaccessibility [53,55]-which is also implicated on body weight control [51].…”
Section: Events Related To Blood Testing or To The Participants' Baseline Cardiovascular Conditionmentioning
confidence: 99%
“…Noteworthy is the fact that in DICA-NUTS trial all nuts provided will be acquired from local farmer's cooperatives and small producers; if effective, the study may contribute also to local economic growth by stimulating the consumption of foods locally cultivated. Nut consumption has been related to reducing the severity of atherosclerosis [49][50][51] by acting on intermediary mechanisms such as improving endothelial function, lipid metabolism, and glycemic markers, protecting both DNA and LDL-c from oxidation, decreasing inflammation, altering microbiota, and controlling body weight [52][53][54]. Nuts and seeds may improve serum lipids by reducing cholesterol absorption, increasing bile acid production by stimulation of 7-hydroxylase, inhibiting HMG-CoA reductase, and reducing postprandial lipidemia by their poor lipid bioaccessibility [53,55]-which is also implicated on body weight control [51].…”
Section: Events Related To Blood Testing or To The Participants' Baseline Cardiovascular Conditionmentioning
confidence: 99%
“…A study reported by Ferrari (2020) showed that Brazil nut ingestion increased the expression of nuclear factor E2 (Nrf2), thus increasing the antioxidant response and decreasing lipid peroxidation, besides decreasing the inflammatory response by reducing the levels of C-reactive protein and interleukin-6 (IL-6) in hemodialysis patients. In another study revealed by the same author, the administration of ß-sitosterol in hamsters resulted in a 20% decrease in plasma cholesterol compared to the control group, in addition to a notable reduction in liver cholesterol.…”
Section: Brazil Nut (Bertholletia Excelsa)mentioning
confidence: 99%
“…A Brazilian study evaluated the effects of Brazil nut supplementation (one Brazil nut per day) on total blood cholesterol (TC) and blood glucose in 130 volunteers and found that this supplementation significantly decreased serum levels of both parameters . In addition to these atheroprotective mechanisms, eating Brazil nuts has also been associated with decreased inflammatory biomarkers (IL-1, IL-6, INF γ, TNF-α) in humans (Ferrari, 2020).…”
Section: Brazil Nut (Bertholletia Excelsa)mentioning
confidence: 99%